2002
DOI: 10.1002/1521-3951(200209)233:2<270::aid-pssb270>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Barrier Height Effect on the Polarizability of a Shallow Magneto-Donor in a Quantum Box

Abstract: PACS: 73.21.La; 73.21.Hb The polarizability is estimated for a shallow donor confined to move in a quantum box (QB) with a uniform magnetic field. In this work, the Hass variational method within the effective mass approximation is used in the case of an infinite and a finite barrier potential. We present our results as a function of the size of the box and the intensity of the magnetic field. It is found, that the polarizabilities decrease with decreasing size of the box, reach a minimum value at a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…18 The polarizability was estimated by Messaoudi et al for a shallow donor confined to move in a QD with a uniform magnetic field using the Hass variational method in the case of an infinite and a finite barrier potential. 19 It was found that the finite barrier-height effect was important for high fields and large QDs.…”
Section: Introductionmentioning
confidence: 99%
“…18 The polarizability was estimated by Messaoudi et al for a shallow donor confined to move in a QD with a uniform magnetic field using the Hass variational method in the case of an infinite and a finite barrier potential. 19 It was found that the finite barrier-height effect was important for high fields and large QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Osorio et al [21] have presented the electric field direction dependence of the binding energy and the polarizability of donor impurities in GaAs-GaAlAs quantum wires. El Messaoudi et al have reported on the polarizability of a magneto-donor in a quantum box [22] and quantum wire [23].…”
Section: Introductionmentioning
confidence: 99%